Effects of long-term exposure to high altitude on brain structure in healthy people: an MRI-based systematic review and meta-analysis - Luo, Qiao; Zhang, Jie-Xin; Huang, Shuo; Hu, Yong-He; Wang, Han; Chen, Xin (Frontiers in Psychiatry, 2023)
Abstract Purpose To conduct a systematic review and meta-analysis of observational studies of brain MRI, this paper assesses the effects of long-term exposure to high-altitude on brain structures in healthy people. Methods Observational studies related to high-altitude, brain and MRI were systematically searched based on data retrieved from PubMed, Embase and Cochrane Library. The timescale for collecting literature was from the establishment of the databases to 2023. NoteExpress 3.2 was used to manage the literature. Two investigators performed literature screening and data extraction based on inclusion criteria, exclusion criteria, and literature quality. The quality of the literature was assessed using the NOS Scale. Finally, meta-analysis of included studies was performed using Reviewer Manager 5.3. Results Initially,3626 articles were retrieved. After screening,16 articles (n=756) were included in the systematic review, and meta-analysis was performed on 6 articles (n=350). The overall quality of the included articles was at medium level, with a mean NOS score of 5.62. The results of meta-analysis showed that the differences between the HA group and LA group were not statistically significant, in total GM volume (MD: -0.60, 95% CI: -16.78 to 15.58, P=0.94), WM volume (MD: 3.05, 95% CI: -15.72 to 21.81, P=0.75) and CSF volume (MD: 5.00, 95% CI: -11.10 to 21.09, P=0.54).The differences between HA and LA in FA values of frontotemporal lobes were not statistically significant: right frontal lobe (MD:-0.02, 95% CI:-0.07~0.03, P=0.38), left frontal lobe (MD:0.01, 95% CI:-0.02~0.04, P=0.65), right temporal lobe (MD:-0.00, 95% CI:-0.03~0.02, P=0.78) and left temporal lobe (MD:-0.01, 95% CI:-0.04~0.02, P=0.62). However, there were significant differences in GM volume, GM density and FA values in local brain regions between HA group and LA group. Conclusion Compared with LA area, there were no significant differences in total GM, WM and CSF volumes in healthy people living at high-altitude area for long-term, while there were significant differences in GM volume and FA values in local brain regions. Long-term exposure to high-altitude area caused the adaptive structural changes in local brain regions. Since heterogeneity existed between the studies, further studies are needed to uncover the effects of high-altitude on brain of healthy people.